Interconfessional dialogue in modern Ukraine: impulses, conditions, purpose, subjects, levels of understanding - Gorkusha, Oksana (Ukrai͏̈ns'ke relihijeznavstvo, 2017)
The article by Oksana Horkusha "Interconfessional dialogue in modern Ukraine: impulses, conditions, purpose, subjects, levels of understanding" analyzes the motives, conditions, goals, subjects and levels of understanding of the interconfessional dialogue in contemporary Ukraine. Interconfessional dialogue cannot have a purpose in itself. Different confessions reach agreement only in the process of such dialogue, which are carried out by mutually viable actors who have a common goal, are in the same cultural-historical context, a definite problem, for the solution of which is used by adequate dialogue platforms, methods and instruments.